Phytochemical Investigation and Anti-Inflammatory Activity of the Leaves of Machilus japonica var. kusanoi - Li, Shiou-Ling (Molecules, 2020)
In a series of anti-inflammatory screenings of lauraceous plants, the methanolic extract of the leaves of Machilus japonica var. kusanoi (Hayata) J.C. Liao showed potent inhibition on both superoxide anion generation and elastase release in human neutrophils. Bioassay-guided fractionation of the leaves of M. japonica var. kusanoi led to the isolation of twenty compounds, including six new butanolides, machinolides A–F (1–6), and fourteen known compounds (7–20). Their structures were characterized by 1D and 2D NMR, UV, IR, CD, and MS data. The absolute configuration of the new compounds were unambiguously confirmed by single-crystal X-ray diffraction analyses (1, 2, and 3) and Mosher’s method (4, 5, and 6). In addition, lignans, (+)-eudesmin (11), (+)-methylpiperitol (12), (+)-pinoresinol (13), and (+)-galbelgin (16) exhibited inhibitory effects on N-formyl-methionyl-leucyl-phenylalanine/cytochalasin B (fMLP/CB)-induced superoxide anion generation in human neutrophils with IC(50) values of 8.71 ± 0.74 μM, 2.23 ± 0.92 μM, 6.81 ± 1.07 μM, and 7.15 ± 2.26 μM, respectively. The results revealed the anti-inflammatory potentials of Formosan Machilus japonica var. kusanoi.